Predictions of the Chinese Forest Frog (Rana chensinensis) Distribution Pattern Under Climate Change up to 2090s - Ying Fu; Juanjuan Lu; Pinhong Yang; Jie Pi (Biology)
The Chinese forest frog (Rana chensinensis) has high ecological and economic value and is an ecologically important species that is very sensitive to environmental changes. However, climate change and increasing human activity are posing growing threats to its natural habitat. To address these challenges, this study aimed to predict the current and future geographic distribution of the Chinese forest frog and to identify the environmental drivers influencing its habitat suitability. Here, the optimized MaxEnt and Biomod2 were used to assess 127 species occurrence records and 22 environmental variables and model and analyze changes in the geographic distribution of the Chinese forest frog in different periods. The environmental factors underlying geographical distribution changes and migration trends in distribution areas under climate change were assessed. The optimized MaxEnt model generated the best predictions, showing that the current most highly suitable areas are located in Chongqing, Sichuan, and Gansu provinces. The optimized MaxEnt model demonstrated exceptionally high predictive accuracy, with mean AUC values of 0.968 ± 0.000 and TSS values of 0.800 ± 0.089. The total area of the current potentially suitable habitat was estimated at 426 × 104 km2. The principal ecological factors influencing the distribution of the Chinese forest frog are Bio9, Bio10, and human activity. Under future scenarios, the potentially suitable habitat for the Chinese forest frog is projected to shift westward and southward. Compared to the current situation, the potentially suitable habitat for the Chinese forest frog is expected to significantly shrink across all four future scenarios (2050s-SSP126, 2050s-SSP585, 2090s-SSP126, and 2090s-SSP585), posing serious threats to its survival. This study not only identifies the key ecological factors limiting the potential distribution of the Chinese forest frog but also provides a scientific basis and data support for the development of conservation strategies and habitat restoration efforts.